Into the volcano : a graphic novel - Wood, Don, 1945- (New York : Blue Sky Press, 2008)
While their parents are away doing research, brothers Duffy and Sumo Pugg go with their cousin, Mister Come-and-Go, to Kokalaha Island, where they meet Aunt Lulu and become trapped in an erupting volcano.
Kirkus Review.
School Library Journal starred.
Voice of Youth Advocates (V.O.Y.A.).
5.9
3-6
Keywords: Brothers -- Comic books, strips, etc. -- Juvenile fiction; Islands -- Comic books, strips, etc. -- Juvenile fiction; Volcanoes -- Comic books, strips, etc. -- Juvenile fiction; Adventure and adventurers -- Fiction; Brothers -- Fiction; Cartoons and comics; Islands -- Fiction; Volcanoes -- Fiction; Adventure fiction; Brothers -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Islands -- Comic books, strips, etc. -- Fiction; Volcanoes -- Comic books, strips, etc. -- Fiction; Adventure fiction; Graphic novels